POSTOPERATIVE REHABILITATION FOLLOWING ANTERIOR CRUCIATE LIGAMENT (ACL) RECONSTRUCTION: STAGES, PROTOCOLS AND THEIR ROLE IN PREVENTING REINJURY - Marcelina Broda,; Kinga Dyndał,; Anna Hawryluk,; Patrycja Jędrzejewska-Rzezak,; Kamil Marzec,; Aleksandra Mokrzycka,; Izabela Szczap,; Katarzyna Urbańska,; Adam Żuczek,; Olga Żuczek, (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and purpose: An anterior cruciate ligament (ACL) injury is one of the most common knee joint injuries, particularly among athletes. Its reconstruction is one of the most frequently performed orthopedic procedures, enabling a return to full physical function. However, a crucial component of recovery is a well-planned and consistently implemented postoperative rehabilitation program, which helps reduce the risk of reinjury. This review discusses the individual stages of rehabilitation, the methods used, and their role in minimizing the aforementioned risk.Material and methods: A comprehensive review and analysis of the literature from 2000 to 2025 was conducted using the PubMed, Google Scholar, Scopus, and Web of Science databases (including randomized controlled trials, meta-analyses, and guidelines). The focus was on various rehabilitation methods following ACL reconstruction and their impact on reducing the risk of reinjury.Brief description of the state of knowledge: Current guidelines and studies identify four phases of rehabilitation: early, intermediate, late, and return to sport. Modern rehabilitation protocols vary in terms of progression rate, techniques used, and tools for assessing therapy outcomes. The psychological aspect is also emphasized, as fear of reinjury can have a significant impact on recovery.Conclusions: Rehabilitation programs based on functional criteria and individualization allow for precise adaptation of therapeutic interventions to the patient’s needs at different stages of the recovery process, thereby significantly reducing the risk of reinjury. Moreover, modern technologies such as biofeedback, virtual reality, and biomechanical analysis can enhance the effectiveness of therapy by improving exercise precision and enabling better monitoring of the patient’s progress.